An environmental analysis of the Type Ib SN 2019yvr and the possible presence of an inflated binary companion. Issue 3 (27th December 2021) - Sun, Ning-Chen; Maund, Justyn R; Crowther, Paul A; Hirai, Ryosuke; Kashapov, Amir; Liu, Ji-Feng; Liu, Liang-Duan; Zapartas, Emmanouil
ABSTRACT: SN 2019yvr is the second Type Ib supernova (SN) with a possible direct detection of its progenitor (system); however, the spectral energy distribution (SED) of the pre-explosion source appears much cooler and overluminous than an expected helium-star progenitor. Using Hubble Space Telescope ( HST ) images and MUSE integral-field-unit (IFU) spectroscopy, we find the SN environment contains three episodes of star formation; the low ejecta mass suggests the SN progenitor is most likely from the oldest population, corresponding to an initial mass of 10.4^+1.5_-1.3 M ⊙ . The pre-explosion SED can be reproduced by two components, one for the hot and compact SN progenitor and one for a cool and inflated yellow hypergiant (YHG) companion that dominates the brightness. Thus, SN 2019yvr could possibly be the first Type Ib/c SN for which the progenitor's binary companion is directly detected on pre-explosion images. Both the low progenitor mass and the YHG companion suggest significant binary interaction during their evolution. Similar to SN 2014C, SN 2019yvr exhibits a metamorphosis from Type Ib to Type IIn, showing signatures of interaction with hydrogen-rich circumstellar material (CSM) at >150 d; our result supports enhanced pre-SN mass-loss as an important process for hydrogen-poor stars at the lower mass end of core-collapse SN progenitors.